Experimental and numerical study of polishing of 2024 aluminum alloy using acoustics energy. (January 2022) - Beigmoradi, Sajjad; Vahdati, Mehrdad
Abstract: Producing components with a high-quality surface is one of the most demanding requests in different fields of industries such as aerospace, medical, automotive, electrical, and so on. Collision of the abrasive powders to the workpiece is a convenient method for polishing the components. There are different techniques to provide kinetic energy in the abrasive powders. In this study, acoustic energy was employed to generate kinetic motion in abrasive powders to polish aluminum workpieces in the low-frequency range, which is here named acoustic abrasive polishing. This study contains experimental and numerical studies of the acoustic polishing process. At the numerical phase, a hybrid approach based on finite element, boundary element, and discrete element methods was used to simulate polishing and study the mechanism of the process in micro scale. The suitable frequency and wave shape for the most efficient polishing process was predicted utilizing the discrete element method. Then, at the experimental phase, effects of the process parameters on the surface quality were investigated. The optimum polishing conditions were achieved, and the surface characteristics of the optimal case were discussed. It was observed that the best-machined workpiece in the experimental tests belongs to the case with the maximum tangential contact force on its surfaces according to the numerical simulations.